The effects of blended learning on university students' reading comprehension - Dagnachew Tsegaye; Girma Gezahegn Belihu (Universitas Negeri Semarang, 2024)
There is no one-size-fits-all method of teaching and learning, as blended learning instruction may demonstrate. The aim of this research was to examine the effects of blended learning (BL) on university students' reading comprehension. The study involved 45 first-year university students, with 23 in the experimental group and 22 in the control group, utilizing a quasi-experimental design with a quantitative approach. Data were gathered through pre-posttest reading comprehension exams adapted from the TOEFL (2023). Following the pretest, the experimental group received blended learning instruction via Moodle, engaging in 16 weeks of intervention over three hours per week. Reading passages and activities were adapted from Communicative English Skills I materials and integrated into the Moodle platform with e-learning elements. Data analysis employed mean calculations, independent samples t-tests, paired samples t-tests, and effect size measures. The pretest revealed no statistically significant differences in overall reading comprehension between the two groups (t =.797, p =.430). However, in the post-test, the experimental group achieved an average mean score of 87.2, whereas the control group averaged 77.6. Significant differences emerged between the groups (t = 3.904, p =.000). The study demonstrated that the experimental group showed statistically significant differences in reading comprehension across all categories compared to the control group. Future research could explore blended learning's influence on other English language skills and its effects across various grade levels, providing valuable insights for English language educators and curriculum developers seeking to integrate blended learning approaches into their programs.